Safety information perception, forewarning & forecast of Chinese small reservoir based on risk classification. Issue 1 (June 2020) - Lu, Qiling; Fang, Weihua; He, Qi; Wang, Xue; Na, Wei
Abstract: In order to effectively manage more than 90000 small reservoirs in China, aiming at their characteristics, based on engineering classification, this article established a system of safety information perception, early warning and prediction based on safety risk classification in terms of the safety risk factors such as occurrence environment, structural materials, supervision and management, and accident loss. It solved the standardization and pertinence problems of small reservoir risk management in China.